2001
DOI: 10.1038/89945
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase-activated receptor-2 and hyperalgesia: A novel pain pathway

Abstract: Using a combined pharmacological and gene-deletion approach, we have delineated a novel mechanism of neurokinin-1 (NK-1) receptor-dependent hyperalgesia induced by proteinase-activated receptor-2 (PAR2), a G-protein-coupled receptor expressed on nociceptive primary afferent neurons. Injections into the paw of sub-inflammatory doses of PAR2 agonists in rats and mice induced a prolonged thermal and mechanical hyperalgesia and elevated spinal Fos protein expression. This hyperalgesia was markedly diminished or ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
423
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(443 citation statements)
references
References 39 publications
17
423
1
2
Order By: Relevance
“…8,10 Proteases that activate PAR 2 are released and activated during inflammation and injury, and PAR 2 controls responses to these insults, with effects on gastrointestinal secretion, motility, inflammation, and pain. 1,3,5,[11][12][13] We investigated the role of PAR 2 and proteases that activate PAR 2 in enteritis induced by toxin A (TxA) from Clostridium difficile. TxA-induced enteritis in rodents parallels the human infection, a common iatrogenic illness in patients receiving antibiotics.…”
Section: Conclusion-parmentioning
confidence: 99%
“…8,10 Proteases that activate PAR 2 are released and activated during inflammation and injury, and PAR 2 controls responses to these insults, with effects on gastrointestinal secretion, motility, inflammation, and pain. 1,3,5,[11][12][13] We investigated the role of PAR 2 and proteases that activate PAR 2 in enteritis induced by toxin A (TxA) from Clostridium difficile. TxA-induced enteritis in rodents parallels the human infection, a common iatrogenic illness in patients receiving antibiotics.…”
Section: Conclusion-parmentioning
confidence: 99%
“…These responses to tryptase are desensitized by selective PAR2 agonists, suggesting that tryptase activates PAR2. Moreover, the hyperalgesic effects of tryptase in the skin are diminished in PAR2ko mice (33). A recent report has questioned the capacity of tryptase to activate PAR2 (44).…”
Section: Tryptase and Trypsin May Activate Par2 In The Inflamed Airwaymentioning
confidence: 99%
“…Intraplantar injection of PAR 2 -activating peptide, trypsin or mast cell tryptase at doses that did not cause inflammation, provoked thermal and mechanical hyperalgesia. The same injections also caused activation of nociceptors at the spinal level, as followed by an increased fos expression in the superficial laminae (I and II) of the dorsal horn (Vergnolle et al 2001a). Moreover, this study showed that PAR 2 -deficient mice developed significantly less inflammatory hyperalgesia in response to intraplantar injection of formalin or the mast cell degranulator compound 48/80 (Vergnolle et al 2001a).…”
Section: Involvement Of Par 2 Activation In Inflammatory Hyperalgesiamentioning
confidence: 99%
“…Since PAR 2 agonists caused inflammation, we first defined doses of PAR 2 agonists that did not cause any signs of inflammation, by following oedema, granulocyte recruitment, prostaglandin release and blood flow (Vergnolle et al 2001a). Then, we used this sub-inflammatory dose to investigate whether or not it was capable of inducing hyperalgesia in response to a thermal or mechanical stimulation.…”
Section: Involvement Of Par 2 Activation In Inflammatory Hyperalgesiamentioning
confidence: 99%